2020
DOI: 10.3389/feart.2020.00308
|View full text |Cite
|
Sign up to set email alerts
|

Upward Expansion of Supra-Glacial Debris Cover in the Hunza Valley, Karakoram, During 1990 ∼ 2019

Abstract: Supra-glacial debris cover is key to glacier ablation through increasing (thin debris layer) or decreasing (thick debris layer) melt rates, thereby regulating the mass balance of a glacier and its meltwater runoff. The thickening or lateral expansion of supra-glacial debris cover correlates with a reduction of glacier ablation and, consequently, runoff generation, which is also considered to be an influential factor on the rheology and dynamics of a glacierized system. Studies on supra-glacial debris cover hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 99 publications
1
24
0
Order By: Relevance
“…While slope thresholds are region-dependent, the minimum slope obtained when filtering the debris covered glaciers by area is consistent with other areas, for ex. 6.7º in the Hunza (Xie et al, 2020a). Both the area and surface slope have a skewed distribution (Fig.…”
Section: Controls On Supraglacial Pond and Vegetation Coveragementioning
confidence: 95%
See 2 more Smart Citations
“…While slope thresholds are region-dependent, the minimum slope obtained when filtering the debris covered glaciers by area is consistent with other areas, for ex. 6.7º in the Hunza (Xie et al, 2020a). Both the area and surface slope have a skewed distribution (Fig.…”
Section: Controls On Supraglacial Pond and Vegetation Coveragementioning
confidence: 95%
“…Glacier tongues here descend to lower elevations (~3,700 m to 4,400 m compared to ~ 4,700 to 4.900 m in the western part) which, in conjunction with the more humid, monsoon-influenced climate might favour vegetation growth. Development of vegetation (mostly shrubs) has been noted on stagnant, thick debris-covered tongues in other areas of the world (Xie et al, 2020a;Tampucci et al, 2016), and was found to be increasing in certain glacierized areas such as the Alps as a consequence to climatic change and declining glaciation (Vezzola et al, 2016). As vegetation typically will only develop on stagnant surfaces that are no longer undergoing substantial gravitational reworking, its presence is also an indication of glacier inactivity and later stages of decay.…”
Section: Supraglacial Vegetationmentioning
confidence: 98%
See 1 more Smart Citation
“…r 0.64, r 2 0.41, adjusted r 2 0.37, F(1,17) 11.72 N 19 p-value March temp 0.003 Dependent variable: mean-SLA, independent variable December-January precipitation r 0.68, r 2 0.47, adjusted r 2 0.44, F(1,17) 14.95 N 19 p-value December-January precipitation 0.001 Dependent variable: mean-SLA, Independent variables: December-January precipitation, March temperature multiple r 0.77, r 2 0.6, adjusted r 2 0.55, F(2,16) 12.03 N 19 p-value December-January precipitation 0.01 March temp 0.03 Icefields, but also in the smaller mountain glaciers in their periphery. In recent decades, expansion of debris-covered ice areas has also been observed in the Himalayas, Karakorum (Bolch et al, 2008;Bhambri et al, 2011;Kirkbride and Deline, 2013;Xie et al, 2020), Caucasus (Tielidze et al, 2020) and the European Alps (Mölg et al, 2019), mostly at decadal to subdecadal scale.…”
Section: Increase In Debris-covered Areamentioning
confidence: 99%
“…Debris-covered glaciers are a special type of glacier [21,22]. The surfaces of mountain glaciers are frequently covered in supraglacial debris, whose spectral characteristics are similar to those of rocks and soil at the foot of the mountain [21,23], making them hard to distinguish from rock glaciers and periglacial areas [24]. Particularly in the Tibetan Plateau, owing to the influence of the monsoon climate, frequent cloud activity occurs during the glacier melting period.…”
Section: Introductionmentioning
confidence: 99%